(ARTICLE RETRACTED) The Relation of Gender and Feminism in Islamic Jurisprudence - Fokky Fuad Wasitaatmadja; Susianto susianto; Suartini Supendi (Ijtimā iyya Journal of Muslim Society Research, 2020)
This article is RETRACTED, because has been publish before at Center for Open in Science (COAS) Open Journal for Legal Studies (OJLS) on Vol. 3 No. 2, 2020. if you want to read and cite this article, please visit http://centerprode.com/ojls/ojls0302/coas.ojls.0302.04125w.html